Woman with Pregnancy and Lactation-Associated Osteoporosis (PLO). (12th November 2020) - Bazgir, Nasrin; Shafiei, Elham; Hashemi, Neda; Nourmohamadi, Hassan
Abstract : Osteoporosis is a disease known to reduce bone density and to damage bone microarchitecture leading to increased fracture risk. Osteoporosis is one of the most common diseases among the middle aged and elderly people that impose high costs on the community. So far, despite rare cases of pregnancy and lactation-associated osteoporosis (PLO) reported in Iran, it can be treated with accurate diagnosis. Patient Introduction . A 24-year-old woman was referred to the outpatient rheumatologic clinic after the cesarean section during the first pregnancy with severe back pain. In the thoracolumbar radiographs, a loss of vertebral height in the T11 to L5 vertebra was recognized. Other complaints were abdominal pain and anemia. In order to evaluate the gastrointestinal disease and celiac, the patient underwent gastrointestinal and hematologic workup. Ultimately, secondary causes of the osteoporosis were excluded. Based on the patient's clinical course, imaging finding, and exclusion of other causes of osteoporosis, the patient was diagnosed with PLO. Conclusion . Clinicians should be aware of PLO as rare complication of pregnancy. The situation should be particularly considered in females offering from new onset back pain in the third trimester of pregnancy or breastfeeding period.